No evidence of beneficial effects of plasmapheresis in natalizumab-associated PML. (21st March 2017) - Landi, Doriana; De Rossi, Nicola; Zagaglia, Sara; Scarpazza, Cristina; Prosperini, Luca; Albanese, Maria; Buttari, Fabio; Mori, Francesco; Marfia, Girolama Alessandra; Sormani, Maria Pia; Capra, Ruggero; Centonze, Diego
Abstract : Objective: To examine retrospectively the effects of plasmapheresis (PLEX) on the survival and clinical outcomes of patients with multiple sclerosis (MS) and natalizumab (NTZ)–associated progressive multifocal leukoencephalopathy (PML). Methods: The medical literature was searched for the terms natalizumab and progressive multifocal leukoencephalopathy. A total of 193 international and 34 Italian NTZ-PML cases were included. Clinical outcome was determined by comparing the patients' clinical status at PML diagnosis with status after PML resolution. The effects on survival and clinical outcome of PLEX, sex, age, country, pre-PML Expanded Disability Status Scale score, NTZ infusion number, prior immunosuppressant exposure, PML symptoms, PML lesion location at diagnosis, CSF JC virus status and copies, additional PML treatments and steroids, and PML immune reconstitution inflammatory syndrome (IRIS) development were investigated with both univariate and multivariate analyses. Results: A total of 219 NTZ-PML cases were analyzed, and 184 (84%) underwent PLEX, which did not reduce the mortality risk or the likelihood of poor vs favorable outcomes. Country was predictive of mortality and poor outcome, while PML-IRIS development was predictive of poor outcome. Conclusions: PLEX did not improve the survival or clinical outcomes of Italian or international patients with MS and NTZ-PML, suggesting that this treatment should be performed cautiously in the future. Classification of evidence: This study provides Class III evidence that for patients with NTZ-PML, PLEX does not improve survival. The study lacks the statistical precision to exclude an important benefit or harm of PLEX.